A Qualitative Inquiry of Politeness Approaches through Gender Category: Evidences from University Students in Aceh - Saiful Akmal; Halimatun Husna; Titin Arifa Maulida; Muhammad Farkhan (Buletin Al-Turas, 2022)
PurposeThis study examines the politeness strategies employed by male and female students and its differences across genders. MethodTo collect data for this qualitative study, 16 participants (with equally eight male and female students) were purposefully opted from the Department of English Language Education at UIN Ar-Raniry Banda Aceh. Eleven situations created to obtain responses from students using a semi-structured interview. The framework of analysis is based on Brown and Levinson’s politeness strategy. Results/FindingsThe study found that male and female students use four politeness strategies. They are (a) bald on record; (b) positive politeness; (c) negative politeness; and (d) off-record. The results indicated that positive politeness is the most prevalent strategy, while bald on record is the least utilized strategy. The politeness strategy was utilized when the participants wanted to express their view to classmates or lecturers. The students performed the strategy because they wanted to support their beliefs or statements unswervingly. Male students used more positive politeness and expresses ideas more directly than female students. ConclusionThe study concluded that both male and female students at the Department of English Language Education, UIN Ar-Raniry Banda Aceh exercised all varieties of politeness strategies. The most applied approaches were positive politeness strategy, followed by the negative politeness strategy, off-record and eventually bald on record as the least frequent politeness strategy.